Plasmid-based target protectors allow specific blockade of miRNA silencing activity in mammalian developmental systems - Knauss, Jennifer L.; Bian, Shan; Sun, Tao (Frontiers in Cellular Neuroscience, 2013)
Over the past decade, microRNAs (miRNAs) have emerged as essential posttranscriptional regulators of gene expression. Though a great deal has been discovered about miRNA genomics, biogenesis, mechanisms and functions, the challenge of attributing phenotypes of altered miRNA expression to specific targets still remains. Here, we apply the existing target protector concept of blocking miRNA action at a single binding site in the 3’untranslated region (3’UTR) of its target to a plasmid-based approach. We optimize and demonstrate target protector efficacy in vitro, where it blocks repression of a luciferase construct and an endogenous protein. Using the developing mouse cortex as a model, we validate that target protectors are effective in vivo, where protectors for the miR-19a binding sites in the Pten 3’UTR alter proliferation and specification of neural progenitors, phenocopying Pten ectopic expression phenotypes. Our study introduces a new tool for analyzing specific miRNA:target interactions across mammalian developmental systems, facilitating further miRNA functional discoveries.